The Co-production of Judaism, Christianity, and Islam (Brepols, 2026)
Judaism, Christianity, and Islam have always formed, re-formed, and transformed themselves in conversation. That is, these religions have come to exist in all their varieties by interacting with, thinking about, and imagining each other. In this sense they are co-produced, linked by a dynamic and ongoing inter-dependence. The fifteen essays collected in this volume explore moments of such religious coproduction from the second to the twenty-first century, from early pilgrimage sites to social media. The case studies range across textual and material cultures, showing how a variety of artefacts, coins, rituals, communities, narratives, theological doctrines, and scholarly concepts, were all co-produced across the three religious traditions. In so doing they present a panorama of possibilities from the past, as well as a taxonomy that can help us think about the future of religious co-production. An introductory essay describes the advantages of approaching the past, present, and future of these religions through the lens of co-production, and reflects on crucial methodological issues related to the understanding of Judaism, Christianity, and Islam as co-produced religions.